PROFILING STUDENTS’ EXPERIENCES AND PERSPECTIVES ON USING VIDEO-TELECONFERENCING APPLICATIONS AS A LEARNING PLATFORM DURING PANDEMIC - Endrian Maulana; Afrianto Daud; Masyhur Masyhur (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2022)
This study aims to capture students’ profiles in terms of using video-teleconferencing (VTC) applications and to identify students’ perspectives on using the video-teleconference applications as a platform for English teaching and learning during the pandemic in the English department in Universitas Riau. This mixed-method study collected data from semi-structured interviews and an online questionnaire. The entire sophomores of the English Study Program of Riau University (n=39 students) were taken as the samples of the research. An analysis model from Miles & Huberman (2007) was used as the method to analyze the collected data. The results show that the majority (56.4 %) of the students used a mobile phone as a learning device and 59% of them relied on their own internet data for learning. The students had both positive and negative perspectives on the VTC applications. Most students thought the VTC-based learning was efficient for them. However, they reported some problems such as an unsupportive learning environment, lack of equipment, and unreliable internet connections. These problems imply that universities should provide more learning facilities for students to make online learning more effective.